Developing the public health workforce in Asia - Evans, Tim G; Ahmed, Syed Masud (© 2014 Taylor and Francis, 2017)
This book chapter was published in Routledge Handbook of Global Public Health in Asia [© 2014 Taylor and Francis] and The Journal's website is at: http://www.citeweb.info/20141015102